2007
DOI: 10.1364/ol.32.002046
|View full text |Cite
|
Sign up to set email alerts
|

High-speed all-optical switching in ion-implanted silicon-on-insulator microring resonators

Abstract: We demonstrate high-speed all-optical switching via vertical excitation of an electron-hole plasma in an oxygen-ion implanted silicon-on-insulator microring resonator. Based on the plasma dispersion effect the spectral response of the device is rapidly modulated by photoinjection and subsequent recombination of charge carriers at artificially introduced fast recombination centers. At an implantation dose of 1 x 10(12) cm(-2) the carrier lifetime is reduced to 55 ps, which facilitates optical switching of signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 12 publications
2
39
0
1
Order By: Relevance
“…The resonance frequency of the resonator at site n = 0 is assumed to be biased and periodically modulated in time. This can be accomplished by modulation of the microcavity refractive index using various physical mechanisms such as free-carrier-plasma dispersion and electro-optic effects [39][40][41][42]. In CROW systems, light transport can be described by coupled-mode theory [18,25,27,28], which reproduces with excellent accuracy the results obtained by FDTD numerical simulations [21,25,27].…”
Section: Photonic Structure and Floquet Analysismentioning
confidence: 74%
“…The resonance frequency of the resonator at site n = 0 is assumed to be biased and periodically modulated in time. This can be accomplished by modulation of the microcavity refractive index using various physical mechanisms such as free-carrier-plasma dispersion and electro-optic effects [39][40][41][42]. In CROW systems, light transport can be described by coupled-mode theory [18,25,27,28], which reproduces with excellent accuracy the results obtained by FDTD numerical simulations [21,25,27].…”
Section: Photonic Structure and Floquet Analysismentioning
confidence: 74%
“…With the 3 dB line width (δf) of the microring resonator determined by solving eq 4, the corresponding analytic solution for the quality factor (Q) of the microring resonator is derived as (5) Particularly, the optical intensity can be enhanced when the propagation wavelength is exactly located at the resonant wavelength of the microring resonator. The traveling wave in the microring waveguide interferes constructively with the input optical field, and the optical intensity magnification is built up in the microring resonator when the optical field travels with a phase-shift of an integral multiple of 2π in one round trip.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Applications would include optical buffering [7], all-optical wavelength conversion [8], and all-optical computation [9], [10]. Almeida et al and Foerst et al have recently demonstrated an all-optical modulator with single-photon absorption (SPA) based carrier injection using visible light [11], [12]. This approach has severe limitations; because of the disparate wavelengths for gate and signal, these devices cannot be cascaded into circuits that require feedback.…”
mentioning
confidence: 99%